Passive Revolution and the Movement against Mass Incarceration: From Prison Abolition to Redemption Script - Robinson, William I. (Social justice, 2019)
In the article, the authors discuss the movement against mass incarceration and the efforts to reform the prison system in the U.S. Also cited are the accomplishments in prison reform like the passage of the First Step Act in 2018, the bill's provisions to bolster prison rehabilitation through educational and training programs, and the groups supporting the bill like the Cato Institute and Americans for Prosperity.